2000
DOI: 10.1155/edr.2000.131
|View full text |Cite
|
Sign up to set email alerts
|

Slowing of Motor Nerve Conduction Velocity in Streptozotocin‐induced Diabetic Rats is Preceded by Impaired Vasodilation in Arterioles that Overlie the Sciatic Nerve

Abstract: Diabetes mellitus produces marked abnormalities in motor nerve conduction, but the mechanism is not clear. In the present study we hypothesized that in the streptozotocin (STZ)-induced diabetic rat impaired vasodilator function in arterioles that provide circulation to the region of the sciatic nerve is associated with reduced endoneural blood flow (EBF) and that these defects precede slowing of motor nerve conduction velocity, and thereby may contribute to nerve dysfunction. As early as three days after the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
188
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 134 publications
(206 citation statements)
references
References 45 publications
17
188
1
Order By: Relevance
“…In our studies, however, we did not detect induction of iNOS in the penis or pyloric sphincter of diabetic rats or in the SH-SY5Y cells when exposed to RA or AGEs (S. Cellek, unpublished observations). Peroxynitrite, the product of the reaction between NO and superoxide in arterioles that provide circulation to the sciatic nerve, has been suggested to be involved in diabetic neuropathy [45,46]. Although we did not detect any increase in nitrotyrosine immunostaining in diabetic rat penis [4], we cannot exclude the possibility that eNOS from nearby blood vessels could produce NO, leading to nitrergic degeneration.…”
Section: Discussioncontrasting
confidence: 72%
“…In our studies, however, we did not detect induction of iNOS in the penis or pyloric sphincter of diabetic rats or in the SH-SY5Y cells when exposed to RA or AGEs (S. Cellek, unpublished observations). Peroxynitrite, the product of the reaction between NO and superoxide in arterioles that provide circulation to the sciatic nerve, has been suggested to be involved in diabetic neuropathy [45,46]. Although we did not detect any increase in nitrotyrosine immunostaining in diabetic rat penis [4], we cannot exclude the possibility that eNOS from nearby blood vessels could produce NO, leading to nitrergic degeneration.…”
Section: Discussioncontrasting
confidence: 72%
“…In their studies, they showed that nerve blood flow was reduced as early as 1 week after diabetes induction. Moreover, Wright and Nukada, and our laboratory have shown that reductions in nerve blood flow preceded the decrease in nerve conduction velocities [34,35]. In addition, we have shown that endothelial-dependent vasodilation of arterioles that provide circulation to the region of the sciatic nerve is impaired by diabetes and the reduction in vascular function also precedes slowing of motor nerve conduction velocity [35,36].…”
supporting
confidence: 52%
“…Moreover, Wright and Nukada, and our laboratory have shown that reductions in nerve blood flow preceded the decrease in nerve conduction velocities [34,35]. In addition, we have shown that endothelial-dependent vasodilation of arterioles that provide circulation to the region of the sciatic nerve is impaired by diabetes and the reduction in vascular function also precedes slowing of motor nerve conduction velocity [35,36]. These studies suggest that vascular dysfunction is an important factor underlying nerve conduction deficits and reduced endoneurial blood flow early in the development of diabetic neuropathy.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations